A comparative historical and typological approach to the Middle Eastern state system : taking Stein Rokkan's ambitions beyond Europe - Mjøset, Lars; Butenschøn, Nils; Harpviken, Kristian Berg (Comparative social research, 2024)
The study of state formation and nation building is a proud tradition. Currently, however, it is difficult to discern a unified research frontier in this field, due to a persistent gap between the more case-based historical focus seen in area studies, and more generalizing approaches inspired by the natural sciences. Showcasing the legacy of Norwegian political scientist and sociologist Stein Rokkan, this volume explores the potential of his work to address this gap. Featuring Rokkan's lecture skeleton methodology, given in Paris 1976, but included here as the first ever English language translation, this collection brings into sharp focus how Rokkan developed a set of methodological tools that allowed the construction of regional models and typological maps for guiding paired or clustered comparisons of state formation and nation building in any world region. Acknowledging Rokkan's key argument that relevant models and maps need to be developed through knowledge about a region's history rather than through formal concepts alone, contributors draw on the full potential of Rokkan's innovations by calibrating them with empirical material from a world region not analysed by Rokkan himself: the Middle East. Thoughtfully reconstructing and upgrading Rokkan's methodology, A Comparative Historical and Typological Approach to the Middle Eastern State System ushers in a new vision in the field of state formation and nation building.